Establishment and analysis of energy consumption model of heavy haul train on large long slope - Lu Qiwei; He Bangbang; Wu Mingzhe; Zhang Zhichun; Luo Jiantao; Zhang Yankui (矿业科学学报, 2018)
AC heavy haul trains could produce a huge of regenerative braking energy when they are running on the long heavy down hill sections.It could reduce costs of coal transportation and improve the power quality if the regeneration braking energy can be used by uphill train in the same power supply section.In order to accurately predict the energy consumption and regenerative braking energy of heavy-haul trains on the large long slope, the single-particle dynamics model of train incoorpatrated with the simplification theory of railway longitudinal section, was used to establish the energy consumption and regenerative braking energy prediction model of a single train based on the train attributes, line condition and running speed.The model had been applied and verified in Shenshuo Railway.The results indicate that the error of the proposed model is generally less than 10%.The model lays a theoretical foundation for the follow-up train diagram layout work with the goal of reducing the total train energy consumption.